Effects of Carbamazepine on blood pressure, serum glucose concentration, lipid profile and prevalence of metabolic syndrome in epileptic patients - Hamo Mahmood, Isam (Tikrit Journal of Pharmaceutical Sciences, 2023)
To investigate the effects of carbamazepine on serum glucose concentrations, lipid profile, blood pressure and prevalence of metabolic syndrome in epileptic patients. Seventy epileptic patients involved in this study. They have primary generalized and partial seizures with duration of treatment with carbamazepine of 11.5±8.37 years. Another 100 apparently healthy individuals were also participated in the study as a control group. Ten ml of venous blood samples were taken from each patient and control after 14 hours fasting. The obtained serum was separated and used for the estimation of glucose concentration, total cholesterol, triglycerides and HDL-cholesterol by using special Kits. LDL-cholesterol was determined by Friedewald equation. Metabolic syndrome was determined according to ATP III criteria for the diagnosis of metabolic syndrome. The patients and controls were matched regarding age and sex. Weight, BMI and waist circumference were statistically not different between patients and controls. Comparison between the measured variables shows significant elevations of the lipid parameters in the patient group as compared with the control group. Non significant differences obtained between serum glucose concentrations and significant low values of BP were obtained in the patient group as compared with the controls. The number of patients and control having metabolic syndrome according to ATP II diagnostic criteria for metabolic syndrome were 4 and 3, respectively. The difference is not significant. This study demonstrated that carbamazepine have no effects on serum glucose concentrations, but have elevating effects on lipid parameters and reducing effects on BP. It has no effects on the prevalence of metabolic syndrome in the epileptic patients